Hope Creek - Dailey, Janet (Dailey, Janet. New Americana series., 2022)
"Old rivalries, new ventures, and long-lost loves converge in the latest novel in New York Times bestselling author Janet Dailey's New Americana series, as the daughter who once walked away from the dark chaos of her childhood returns to her Lowcountry hometown, hoping to put the past to rest... For Kit Teague, the island of Hope Creek, South Carolina, is filled with joyful memories of being out on the water with her beloved father. But her small hometown is also the place where her mother battled mental illness--and lost. Returning home to put her mother to final rest, Kit discovers a family divided by grief--and wounds so deep her twin sister has turned against their father--and Kit. Not only has Viv moved up the creek to join a rival fishing business, she's barricaded herself behind Beau Sutton, the boy Kit once loved from afar. The man who stirs something deep within Kit even now. Amid old-fashioned oyster roasts, starlit outings on the creek and sun-drenched fishing expeditions, Kit finds hope for a new life and renewed love. Neither the whispered scandals of the past nor the rift between their families will keep her from discovering the joy she and Beau can share."-- Provided by publisher.